Evaluasi Sistem Informasi Manajemen : Kriteria dan Metode Pengukuran - Aininta Alivia br Kaban; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
Management information system (MIS) evaluation is an important process for assessing effectiveness and efficiency in organizational decision making. This research identifies criteria such as information quality, user satisfaction, system integration, and performance impact. Evaluation methods used include user surveys, system performance analysis, and case studies. Results show that these criteria and methods complement each other, provide deep insight into the strengths and weaknesses of MIS, and permit the development of MIS that is more responsive to user needs and dynamic organizational environments.